Peeling method and method for processing semiconductor wafer
The method of applying water and then subjecting the protective film on semiconductor wafers to a freezing treatment addresses the challenges of residual contamination and damage during peeling, achieving efficient and damage-free film removal.
Patent Information
- Application Number
- JP2023171650
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-02
- Publication Date
- 2025-04-14
AI Technical Summary
Existing methods for protecting semiconductor wafers, such as using adhesive tapes or forming protective films, often result in residual contamination or damage during peeling due to uneven surfaces and varying adhesiveness.
A method involving the application of a water supply followed by a freezing treatment to reduce the peeling force of a protective film from a semiconductor wafer, thereby minimizing residue and damage.
The method effectively reduces the peeling force of the protective film, allowing for easier removal without causing damage to the semiconductor wafer surface or leaving residues.
Smart Images

Figure 2025062516000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a peeling method and a semiconductor wafer processing method. [Background technology]
[0002] Semiconductor wafers are subjected to processing steps such as a back grinding step while the surface on which the circuits are formed is protected with a protective material. A typical protective material for semiconductor wafers is known to be adhesive tape (e.g., Patent Document 1). As a method for protecting the circuit surface of a semiconductor wafer other than adhesive tape, a method of forming a protective film by applying a liquid composition has been proposed (e.g., Patent Documents 2 to 6). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2015-185641 A [Patent Document 2] Japanese Patent Application Publication No. 10-120965 [Patent Document 3] JP 2000-315668 A [Patent Document 4] JP 2014-212179 A [Patent Document 5] JP 2011-23272 A [Patent Document 6] JP 2014-19889 A Summary of the Invention [Problem to be solved by the invention]
[0004] In recent years, the circuit surface of a semiconductor wafer has become complicated, and it may be difficult to sufficiently fill the unevenness of the circuit surface with an adhesive tape. Therefore, if an attempt is made to improve the embeddability by softening the adhesive constituting the adhesive tape, the adhesive or its constituents may remain on the circuit surface after the adhesive tape that has completed its protective role is peeled off and removed, which may easily cause contamination. In addition, according to the method of forming a protective film by applying a liquid composition to the circuit surface, good embeddability is easily obtained, but a part of the embedded protective film may remain on the circuit surface (especially the uneven part) after the protective film is removed. Furthermore, in both the method using the adhesive tape and the method of forming a protective film, there is a general tendency that if the adhesion to the circuit surface is too low, the protection of the circuit surface is insufficient, and if the adhesion to the circuit surface is increased, residues are easily generated during removal and damage to the circuit surface (e.g., pulling out of bumps, etc.) is easily caused.
[0005] Therefore, an object of the present invention is to provide a novel method for peeling off a protective film from an object to be protected (hereinafter, also simply referred to as "object".) Another related invention is to provide a method for processing a semiconductor wafer using the above method. [Means for solving the problem]
[0006] According to this specification, a method for peeling a protective film covering a surface of an object from the object is provided. Here, the protective film is a film containing a resin material. The method includes supplying water to the protective film and then performing a freezing treatment. By performing a freezing treatment after supplying water in this manner, the peeling force of the protective film from the surface of the object can be effectively reduced, and the load applied to the surface of the object and the protective film itself when removing the protective film can be reduced. This can be advantageous from the viewpoint of suppressing the generation of residues derived from the protective film and preventing damage to the surface of the object.
[0007] In some embodiments, the protective film may be a film formed from a water-dispersed resin composition. The peeling force reduction effect by the freezing treatment after the water supply may be preferably exhibited in a protective film formed from a water-dispersed resin composition (hereinafter, also referred to as a "water-dispersed protective film").
[0008] In some embodiments, the protective film has a water absorption rate of more than 3% based on the water absorption rate measurement described below. The peel force reduction effect by the freezing treatment after the water supply tends to be more pronounced in protective films with a water absorption rate of 3% or more. [Water absorption measurement] A sample having the above protective film provided on the surface of a flat glass plate is immersed in ion-exchanged water at 23° C. for 30 minutes, and the water absorption is calculated from the weight W0 of the above protective film before immersion and the weight W1 after immersion according to the following formula. Water absorption rate [%]=(W1-W0) / W0×100
[0009] In some embodiments, the protective film has a tensile modulus of elasticity of 10 MPa or more at 23° C. A protective film satisfying the above tensile modulus of elasticity is preferable from the viewpoint of protecting an object.
[0010] In some embodiments, the surface of the object may be a surface having a plurality of projections and recesses. The technology disclosed herein can be applied to peeling a protective film from such a surface having a plurality of projections and recesses (hereinafter also referred to as an "uneven surface"), and can effectively reduce the peeling force by the freezing treatment after the water supply.
[0011] In some embodiments, the surface of the object may be a surface of a semiconductor wafer on which a circuit pattern is formed (hereinafter, also referred to as a "circuit surface"). The technology disclosed herein may be applied to peeling a protective film from the circuit surface of a semiconductor wafer, and may effectively exert the effect of reducing the peeling force by the freezing treatment after the water supply.
[0012] According to this specification, a method for processing a semiconductor wafer is provided. The method includes covering the surface of the semiconductor wafer on which a circuit pattern is formed with a protective film containing a resin material; grinding the surface of the semiconductor wafer not covered with the protective film; supplying water to the protective film and then performing a freezing treatment; and peeling and removing the protective film that has been subjected to the freezing treatment. According to the processing method, the freezing treatment after the water supply can effectively reduce the peeling force of the protective film from the circuit surface. This makes it possible to easily remove the protective film from the circuit surface while suppressing the generation of residues derived from the protective film and damage to the surface of the target object.
[0013] In addition, any suitable combination of the elements described in this specification may also be included within the scope of the invention for which patent protection is sought by this application. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a flow diagram showing an embodiment of a peeling method according to the present invention. [Diagram 2] 1(a) to 1(c) are explanatory views illustrating a semiconductor wafer processing method according to one embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Preferred embodiments of the present invention will be described below. Matters necessary for carrying out the present invention other than those specifically mentioned in this specification can be understood by those skilled in the art based on the teachings on carrying out the invention described in this specification and the common general technical knowledge at the time of filing. The present invention can be carried out based on the contents disclosed in this specification and the common general technical knowledge in the relevant field. In the following drawings, the same reference numerals may be used to denote components or parts having the same function, and duplicated descriptions may be omitted or simplified. In addition, the embodiments shown in the drawings are schematic in order to clearly explain the present invention, and do not necessarily accurately represent the size or scale of the product actually provided.
[0016] In this specification, the "base polymer" of the protective film refers to the main component of the polymer components contained in the protective film. Similarly, when the "base polymer" is used for other materials, it refers to the main component contained in the material. In this specification, unless otherwise specified, the "main component" refers to a component contained in more than 50% by weight.
[0017] In this specification, the term "acrylic polymer" refers to a polymer that contains, as a monomer unit constituting the polymer, a monomer unit derived from a monomer having at least one (meth)acryloyl group in one molecule. Therefore, the acrylic polymer in this specification is defined as a polymer that contains a monomer unit derived from an acrylic monomer.
[0018] In addition, in this specification, "acrylic monomer" refers to a monomer having at least one (meth)acryloyl group in one molecule. Here, "(meth)acryloyl group" refers to acryloyl group and methacryloyl group collectively. Therefore, the concept of acrylic monomer here may include both monomers having an acryloyl group (acrylic monomer) and monomers having a methacryloyl group (methacrylic monomer). Similarly, in this specification, "(meth)acrylic acid" refers to acrylic acid and methacrylic acid, and "(meth)acrylate" refers to acrylate and methacrylate collectively. The same applies to other similar terms.
[0019] In addition, in this specification, "weight" may be read as "mass." For example, "wt%" may be read as "mass%," and "parts by weight" may be read as "parts by mass."
[0020] <Water supply - freezing treatment> The peeling method disclosed herein includes, for example, preparing an object (object with protective film) whose surface is covered with a protective film (step S10), supplying water to the protective film (step S20), and performing a freezing process after the water supply (step S30), as shown in FIG. 1. Hereinafter, performing a freezing process after supplying water (water supply) in this manner may be referred to as a "water supply-freezing process". By performing a freezing process after hydrating the protective film by the water supply, the peeling force of the protective film from the object can be effectively reduced. The reason for this, which is not particularly limited, is that the water present at or near the interface between the protective film and the object freezes and expands in volume due to the freezing process after the water supply, which pushes the protective film up from the object surface, reducing the adhesion to the object and reducing the peeling force. The protective film that has undergone the freezing process after the water supply (water supply-freezing process) is typically peeled off from the object at an appropriate timing thereafter (step S40).
[0021] The supply of water to the protective film can be carried out by various methods capable of increasing the amount of water in the protective film. The water supplied to the protective film may be in the form of a liquid, a gas (water vapor), or an intermediate form or a mixture thereof. Specific examples of the method of supplying water to the protective film include, but are not limited to, a method of immersing the protective film in water, a method of applying water to the back surface of the protective film (the surface opposite to the object to be protected), and a method of maintaining the protective film in an environment of high humidity (for example, about 80 to 100% relative humidity). In the method of applying water to the protective film, the method of applying water is not particularly limited, and known methods such as spray application, brush application, casting application, and spin coating can be appropriately adopted. Water may be supplied at room temperature (for example, about 10°C to 35°C), or at a temperature higher or lower than the room temperature.
[0022] Water may be supplied to the protective film through a layer (e.g., a substrate layer or adhesive layer, which will be described later) or member (which may be the object to be protected) adjacent to the protective film. When such a water supplying method is adopted, it is preferable that the layer or member has moisture (water and / or water vapor) permeability or the property of being able to retain moisture, depending on its material or structure. Examples of layers that have moisture permeability due to their structure include porous layers (e.g., layers composed of fibrous aggregates such as nonwoven fabrics, woven fabrics, knitted fabrics, and paper, or foams with an open cell structure), and layers having one or more holes penetrating in the thickness direction (perforated resin sheets, punched metal, etc.).
[0023] The type of water to be supplied to the protective film is not particularly limited. In some embodiments, purified water such as distilled water, ultrapure water, reverse osmosis water (RO water), and ion-exchanged water may be preferably used. In other embodiments, from the viewpoint of availability and cost, one or more types of water selected from natural water (e.g., groundwater, spring water, river water, rainwater, etc.), tap water, industrial water, etc. may be used as the water, and these may be used in combination with the purified water. In addition, the water may be supplied to the protective film in the form of an aqueous liquid containing any additive (e.g., surfactant, colorant such as dye, pH adjuster, etc.) and an organic solvent that can be uniformly mixed with water (e.g., lower alcohol having about 1 to 3 carbon atoms, etc.) to the extent that the effect of the present invention is not significantly impaired. The content of the additive in the aqueous liquid may be, for example, 5% by weight or less, 1% by weight or less, or 0.1% by weight or less. The content of the organic solvent in the aqueous liquid may be, for example, 10% by weight or less, 5% by weight or less, 1% by weight or less, or 0.1% by weight or less.
[0024] The time for supplying water to the protective film (water supply time) is not particularly limited, and can be appropriately set so that the desired peeling force reduction effect can be expressed, for example, by freezing treatment after water supply. In some embodiments, the water supply time can be, for example, 5 seconds or more, 10 seconds or more, 30 seconds or more, 1 minute or more, 3 minutes or more, or 5 minutes or more. The water supply time can be, for example, 6 hours or less, 2 hours or less, 1 hour or less, 30 minutes or less, 20 minutes or less, 15 minutes or less, or 10 minutes or less, and may be less than 10 minutes, less than 7 minutes, less than 5 minutes, less than 2 minutes, or less than 1 minute. It is preferable to shorten the water supply time to the extent that the desired effect is obtained from the viewpoint of shortening the time required for water supply-freezing treatment (and thus the time required for carrying out the peeling method disclosed herein). Also, for example, in an embodiment in which the water supply path to the protective film is limited (for example, an embodiment in which water is mainly supplied from the end face of the protective film due to a non-water-permeable or low-water-permeable layer being disposed on the back side of the protective film), it may be advantageous to make the water supply time relatively long. Note that in an embodiment in which an object (object with protective film) during the period protected by the protective film is subjected to a processing step using water and the water can be absorbed by the protective film, when the protective film is peeled off after the processing step, it may be possible to omit or simplify the operation of newly supplying water to the protective film (for example, shortening the water supply time).
[0025] The treatment temperature and treatment time when the protection film after water supply is subjected to the freezing treatment are not particularly limited, and can be appropriately set so that the desired peeling force reduction effect is expressed. The treatment temperature is suitably less than 0°C, and is usually preferably -1°C or less, -3°C or less, or -5°C or less, and may be -10°C or less, -20°C or less, or -30°C or less. The treatment temperature can be, for example, -80°C or more, and is usually advantageously -60°C or more, and may be -50°C or more, -40°C or more, -30°C or more, -20°C or more, or -10°C or more. A lower treatment temperature can produce the desired peeling force reduction effect by a shorter freezing treatment. This can shorten the time required for the water supply-freezing treatment (and thus the time required for carrying out the peeling method disclosed herein). On the other hand, in some embodiments, it may be advantageous not to lower the treatment temperature too much, taking into account the degree of low temperature resistance of the object and the protection film.
[0026] The cooling means for carrying out the freezing treatment is not particularly limited, and various known cooling means can be used alone or in combination. The cooling may be direct cooling, indirect cooling, or an intermediate or composite cooling between them. Specific examples of the cooling means include a method of maintaining the material in an environment adjusted to the freezing treatment temperature, a method of blowing cold air, a method of contacting the material with a cold plate, a method of blowing an aerosol spray, a method of contacting the material with a refrigerant pipe, and a method of electronic cooling such as a Peltier element. The cooling means can be used alone or in appropriate combination of two or more means. The treatment time in the freezing treatment is not particularly limited, and can be appropriately set so as to obtain the desired treatment effect. The above treatment time can be, for example, 1 second or more, 3 seconds or more, 5 seconds or more, 10 seconds or more, 30 seconds or more, 1 minute or more, 3 minutes or more, 5 minutes or more, 10 minutes or more, or 15 minutes or more, and can be, for example, 6 hours or less, or 2 hours or less, or 1 hour or less, or 30 minutes or less, 25 minutes or less, or 20 minutes or less, or 15 minutes or less, or 10 minutes or less. Depending on the type of cooling means used, etc., in some embodiments, the above treatment time can be, for example, 2 minutes or less, 1 minute or less, 30 seconds or less, or 15 seconds or less.
[0027] The peeling method disclosed herein may include subjecting a protective film covering an object to the above-mentioned water supply-freezing treatment, and then peeling the protective film from the object. The peeling of the protective film may be performed in the room temperature range (for example, about 10°C to 35°C), or may be performed at a temperature higher or lower than the room temperature range. From the viewpoint of reducing the load applied to the object during peeling, it is advantageous to perform the peeling at a temperature higher than 0°C. The peeling temperature may be, for example, 1°C or higher, 5°C or higher, 10°C or higher, 15°C or higher, or 20°C or higher, and may be 30°C or higher, 40°C or higher, or 50°C or higher. In some embodiments, the peeling temperature is usually appropriate to be about 90°C or lower, advantageously 70°C or lower, and preferably 55°C or lower, and may be 45°C or lower, 35°C or lower, or 25°C or lower, from the viewpoint of suppressing the deterioration of operability due to softening of the protective film and re-adhesion (increase in adhesion) to the surface of the object. The peeling temperature refers to the environmental temperature at which the peeling operation is performed. After the water supply-freezing process, it is preferable to perform an operation of peeling off and removing the protective film after maintaining the environmental temperature for a certain period of time. The time (maintenance time) for maintaining the protective film at the environmental temperature after the water supply-freezing process can be, for example, 10 seconds or more, preferably 30 seconds or more, and may be 1 minute or more, 2 minutes or more, or 3 minutes or more. The maintenance time can be, for example, 6 hours or less or 2 hours or less, and in some embodiments, from the viewpoint of suppressing reattachment (increase in adhesion) of the protective film to the object surface, it is advantageous to maintain it for about 1 hour or less, preferably 30 minutes or less, and may be 15 minutes or less, 10 minutes or less, or 5 minutes or less.
[0028] The peeling method disclosed herein can be preferably carried out, for example, under the following time conditions. Water supply processing time: 10 seconds to 20 minutes Freezing time: 3 seconds to 25 minutes The above holding time is about 10 seconds to 15 minutes. In some preferred embodiments, by appropriately selecting these time conditions, the stripping methods disclosed herein can be completed in 45 minutes or less (eg, 30 minutes or less).
[0029] The technology disclosed herein is a method for reducing the peeling force (initial peeling force F 0 ) by 20% or more, that is, the peel force reduction rate A calculated by the following formula can be preferably implemented in an embodiment in which it is 20% or more. Peel force reduction rate A [%] = (1-(F WF / F 0 ))×100 In the above formula, F 0 is the initial peeling force of the protective film from the object [N / 20 mm], F WF is the peeling force [N / 20 mm] of the protective film after water supply and peeling treatment. Initial peeling force F 0 The peel strength after water supply-peeling treatment (peeling strength after treatment) F is measured by performing a 180° peel test using a tensile tester at a tensile speed of 300 mm / min in a measurement environment of 23°C and 50% RH. WF is measured by subjecting the protective film to a water supply-peeling treatment, and then performing a 180° peel test at a tensile speed of 300 mm / min using a tensile tester in a measurement environment of 23°C and 50% RH. Note that the initial peel force F may be reduced due to insufficient strength of the protective film or the object (e.g., the occurrence of tearing or cracking). 0 The peel force F after treatment cannot be measured. WF When it is possible to measure the peel strength reduction rate A, for convenience, it can be considered that the peel strength reduction rate A is at least 20%.
[0030] In some embodiments, the peel strength reduction rate A is more preferably 40% or more, even more preferably 60% or more, and may be 70% or more, 75% or more, 80% or more, or 85% or more. The peel strength reduction rate A is preferably 100% (i.e., the post-treatment peel strength F WFIn some embodiments, the peel force reduction rate A may be 99.9% or less, 99.5% or less, 99% or less, or 97% or less. It is advantageous for the peel force reduction rate A not to be too high in terms of preventing the protective film from accidentally falling off the object and appropriately controlling the timing of removing the protective film. The method disclosed herein can be preferably carried out in an embodiment in which the peel force is reduced to such an extent that any of the above-mentioned peel force reduction rates A is satisfied by the water supply-peeling treatment.
[0031] In some embodiments of the presently disclosed technology, the post-treatment peel force F WF From the viewpoint of reducing the load on the object and suppressing residue when peeling off the protective film, the post-treatment peeling force F is suitably less than 5.0 N / 20 mm, preferably less than 4.0 N / 20 mm, and more preferably less than 3.0 N / 20 mm (e.g., less than 2.5 N / 20 mm, less than 2.0 N / 20 mm, or less than 1.5 N / 20 mm). WF may be 0 N / 20 mm, and in some embodiments, may be more than 0 N / 20 mm, for example, 0.1 N / 20 mm or more, or 0.3 N / 20 mm or more. WF A temperature that is not too low can be advantageous in terms of preventing the protective film from accidentally falling off the object and accurately controlling the timing for removing the protective film.
[0032] The technology disclosed herein is directed to an object having a protective film covering the surface (object with protective film), and is characterized in that the peel force (initial peel force F 0 The present invention can be preferably implemented in an embodiment in which the peel force (initial peel force F) of the protective film is reduced by at least 20% (i.e., a peel force reduction rate of 20% or more) by applying the water supply-peeling treatment to an object with a protective film having a peel force of 2.0 N / 20 mm or more, 3.0 N / 20 mm or more, 4.0 N / 20 mm or more, 6.0 N / 20 mm or more, or 8.0 N / 20 mm or more. The technology disclosed herein can also be implemented in an embodiment in which the peel force (initial peel force F) of the protective film from the surface of the object is reduced by at least 20% (i.e., a peel force reduction rate of 20% or more) due to insufficient strength of the protective film or the object, etc.0 The above water supply-peeling treatment is applied to an object with a protective film, for which it is difficult to measure the peeling force of the protective film from the object (peeling force after treatment F WF The peel force can be preferably reduced to such an extent that the measurement of the peel strength becomes possible.
[0033] In some embodiments, the peel force after water supply F is measured after water is supplied to the protective film without performing a freezing treatment. W [N / 20mm] is suitably 1.0N / 20mm or more, preferably 1.5N / 20mm or more, more preferably 2.0N / 20mm or more, 2.5N / 20mm or more, or 3.0N / 20mm or more. W From the viewpoint of water resistance of the protective function, it is preferable that the protective film exhibits the above-mentioned peeling force after water supply F. For example, even when the object with the protective film is subjected to a processing step using water, the protective function of the protective film in the processing step is easily maintained appropriately. W [N / 20mm] may be, for example, 10N / 20mm or less, 7.0N / 20mm or less, or 5.0N / 20mm or less. W is not too high, so that the peel force after treatment F WF The peel strength after water supply F W The water supply in the measurement of is performed according to the water supply conditions in the peeling method disclosed herein. The object with the protective film in the technology disclosed herein is immersed in ion-exchanged water at 23° C. for 10 minutes, and then the post-water-supply peeling force F is measured without performing a freezing treatment. W [N / 20 mm] may satisfy any of the lower limit values described above (and preferably, further satisfy any of the upper limit values described above).
[0034] In some embodiments of the technology disclosed herein, the peel force after the water supply-peeling treatment (post-treatment peel force) F WF [N / 20mm] is the peeling force after water supply F WIt is preferable that the peel strength reduction rate B is 5% or more lower than [N / 20 mm]. In other words, it is preferable that the peel strength reduction rate B calculated by the following formula is 10% or more. Peeling force reduction rate B[%]=(1-(F WF / F W ))×100 Here, the peeling force after water supply F W The water supply in the measurement is carried out according to the water supply conditions in the peeling method disclosed herein as described above, or by immersing the sample in ion-exchanged water at 23°C for 10 minutes. When the peel strength reduction rate B is 10% or more, it is possible to preferably achieve both the water resistance of the protective function and the easy releasability after the water supply-freezing treatment. The peel strength reduction rate B is more preferably 20% or more, further preferably 30% or more, and may be 40% or more, 50% or more, or 60% or more. The peel strength reduction rate B is preferably 100% (i.e., the post-treatment peel strength F WF In some embodiments, the peel force reduction rate B may be 99.9% or less, 99.5% or less, 99% or less, or 97% or less.
[0035] <Protective film> The protective film in the technology disclosed herein is a film containing a resin material. The type of the resin material is not particularly limited, and may be, for example, an acrylic polymer, a rubber polymer, a urethane polymer, an ethylene-vinyl acetate copolymer, a polyester polymer, a polyolefin polymer, a polyether polymer, a silicone polymer, a polyamide polymer, a fluorine polymer, a polyolefin, a composite of these (for example, composite particles with a core-shell structure), or the like. The concept of the rubber polymer includes natural rubber, modified natural rubber (for example, acrylic modified natural rubber), and synthetic rubber. Specific examples of synthetic rubber may be resin materials containing various polymers such as styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber (NBR), butadiene rubber, chloroprene rubber, styrene-butadiene block copolymer, and styrene-isoprene block copolymer as base polymers. The protective film disclosed herein may be formed from a composition (composition for forming a protective film) containing such a polymer in the form of a polymer or partial polymer.
[0036] The form of the protective film-forming composition is not particularly limited, and may be, for example, an aqueous emulsion-type composition in which the polymer is dispersed in an aqueous solvent, a solvent-type composition in which the polymer is dissolved in an organic solvent, or an active energy ray (e.g., ultraviolet ray) curable composition containing the polymer in the form of a partial polymer. Among them, a protective film formed from an aqueous emulsion-type composition is preferred. The emulsion particles contained in the aqueous emulsion-type composition do not completely lose their structure even after the protective film is formed, and form grain boundaries within the protective film. Hydrophilic components, hydrophilic functional groups, low molecular weight components, etc. are likely to be unevenly distributed in the grain boundaries, and therefore the grain boundaries tend to be relatively more hydrophilic than the inside of the particles. When the technology disclosed herein is applied to a protective film formed from an aqueous emulsion-type composition, the hydrophilicity of the grain boundaries can be utilized to efficiently deliver the water supplied in the water supply-peeling treatment to the interface with the object or its vicinity, and the effect of reducing the peeling force by the water supply-freezing treatment can be suitably expressed. In addition, the temperature drop caused by the freezing process causes the protective film to shrink, and the water present at the grain boundaries near the interface is pushed out to the interface with the target object. This is also thought to contribute to the reduction in the peeling force caused by the water supply-freezing process.
[0037] Below, regarding the composition used to form a protective film (composition for forming a protective film), an embodiment in which the composition is a composition containing an acrylic polymer as a base polymer (acrylic resin composition) will be mainly described, but it is not intended to limit the application of the technology disclosed herein to protective films formed from acrylic resin compositions (acrylic protective films).
[0038] The protective film in the technology disclosed herein may be formed from an acrylic resin composition containing an acrylic polymer as a base polymer. The acrylic polymer may be a polymer of a monomer component containing one or more acrylic monomers and may contain other monomers as necessary. By adjusting the type and / or content ratio of the monomer constituting the monomer component, the properties such as the SP value and glass transition temperature (Tg) of the polymer, and the tensile modulus of elasticity of the protective film formed from the composition containing the polymer can be adjusted to any appropriate value. In some embodiments, the content of the acrylic monomer in the monomer component may be, for example, 25% by weight or more, preferably 40% by weight or more, more preferably 50% by weight or more (e.g., more than 50% by weight), and may be 60% by weight or more, 65% by weight or more, 70% by weight or more, or 75% by weight or more.
[0039] As the acrylic monomer, any suitable (meth)acryloyl group-containing monomer can be used. In some preferred embodiments, at least an alkyl (meth)acrylate is used as the (meth)acryloyl group-containing monomer. The alkyl (meth)acrylate may be used alone or in combination of two or more.
[0040] As the alkyl (meth)acrylate, any appropriate alkyl (meth)acrylate can be used. Specifically, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, Alkyl (meth)acrylates having an alkyl group having 1 to 20 carbon atoms, such as isononyl acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate (hereinafter, C 1-20 Also called alkyl (meth)acrylate.
[0041] In some embodiments, the monomer component constituting the base polymer (e.g., acrylic polymer) is preferably an alkyl (meth)acrylate (C ) having an alkyl group having 4 to 20 carbon atoms. 4-20 The monomer component preferably contains an alkyl (meth)acrylate having an alkyl group with 4 to 14 carbon atoms, and more preferably contains an alkyl (meth)acrylate having an alkyl group with 4 to 9 carbon atoms. By using these alkyl (meth)acrylates, it is possible to suitably realize a protective film that exhibits an initial peel strength capable of providing the desired protective function during the protection period, and that can be satisfactorily peeled off by carrying out a water supply-peeling treatment. Specifically, the monomer component preferably contains n-butyl acrylate (BA) and / or 2-ethylhexyl acrylate (2EHA), and more preferably contains BA. C 4-20The alkyl (meth)acrylate may be used alone or in combination of two or more kinds.
[0042] C in monomer components 4-20 The content of alkyl (meth)acrylate can be in any suitable range. In some embodiments, the C 4-20 The content of the alkyl (meth)acrylate may be, for example, 10% by weight or more, preferably 20% by weight or more, more preferably 30% by weight or more, and may be 40% by weight or more, 50% by weight or more, 60% by weight or more, 65% by weight or more, or 70% by weight or more. 4-20 The content of alkyl (meth)acrylate may be, for example, 99.5% by weight or less. From the viewpoint of making it easier to exert the effects of using other monomers, it is usually appropriate that it is 99% by weight or less, and it is preferably 97% by weight or less, and it may be 95% by weight or less, 90% by weight or less, 80% by weight or less, 75% by weight or less, or 70% by weight or less. 4-20 The content of alkyl (meth)acrylate in the above range can be advantageous in terms of realizing a protective film having a high initial peel strength and a low peel strength after water supply and peeling treatment. 4-20 The above description regarding the content of alkyl (meth)acrylate is based on the C content in the monomer component. 4-14 Alkyl (meth)acrylate content and C 4-9 This can also be applied to the content of alkyl (meth)acrylate.
[0043] In some embodiments, the monomer component constituting the base polymer is an alkyl (meth)acrylate (C 1-3 It may contain alkyl (meth)acrylate. 1-3 Alkyl (meth)acrylates can be useful for improving the performance of protecting the surface of an object and / or improving the peelability after water supply and freezing treatment by adjusting the Tg of the base polymer, adjusting the tensile modulus of the protective film, and imparting appropriate strength and rigidity to the protective film.1-3 Alkyl (meth)acrylate is C 4-20 It may be used in combination with alkyl (meth)acrylate. 4-20 It may be used as a component of the monomer component that does not contain alkyl (meth)acrylate. In some preferred embodiments, C 4-20 Alkyl (meth)acrylate and C 1-3 It is preferable to use alkyl (meth)acrylate in combination. 1-3 Suitable examples of alkyl (meth)acrylates include methyl methacrylate (MMA) and ethyl methacrylate. 1-3 The alkyl (meth)acrylate may be used alone or in combination of two or more kinds.
[0044] C in monomer components 1-3 The content of alkyl (meth)acrylate can be in any suitable range. In some embodiments, the C 1-3 The content of the alkyl (meth)acrylate may be, for example, 1% by weight or more, and from the viewpoint of easily obtaining a higher usage effect, it may be 3% by weight or more, 6% by weight or more, 8% by weight or more, 10% by weight or more, 15% by weight or more, 20% by weight or more, or 25% by weight or more. 1-3 The content of alkyl (meth)acrylate may be, for example, 80% by weight or less, preferably 60% by weight or less from the viewpoint of flexibility of the protective film, more preferably 50% by weight or less, and may be 50% by weight or less, 40% by weight or less, 30% by weight or less, or 20% by weight or less, or may be 15% by weight or less, or 10% by weight or less. 1-3 It may be substantially free of alkyl (meth)acrylate.
[0045] In some embodiments, the monomer components constituting the base polymer preferably include a nitrogen atom-containing monomer. The nitrogen atom-containing monomer is 1-20It is preferable to use it in combination with an alkyl (meth)acrylate. Any appropriate nitrogen atom-containing monomer can be used as the nitrogen atom-containing monomer. Non-limiting specific examples of the nitrogen atom-containing monomer include cyano group-containing monomers such as acrylonitrile, methacrylonitrile, and 2-cyanoethyl (meth)acrylate; amide group-containing monomers such as (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N-butyl (meth)acrylamide, N-methylol (meth)acrylamide, N-hydroxyethyl (meth)acrylamide, N-methoxymethyl (meth)acrylamide, N-butoxymethyl (meth)acrylamide, and diacetone (meth)acrylamide; aminoethyl (meth)acrylamide; Amino group-containing monomers such as acrylate, N,N-dimethylaminoethyl (meth)acrylate, and t-butylaminoethyl (meth)acrylate; and monomers having a nitrogen atom-containing ring such as N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-vinylmorpholine, N-vinylcaprolactam, and N-(meth)acryloylmorpholine; and the like. The nitrogen atom-containing monomer is preferably a cyano group-containing monomer, and more preferably acrylonitrile. The nitrogen atom-containing monomer can be useful for improving the performance of protecting the surface of the object and / or improving the peelability after water supply and freezing treatment through the adjustment of the Tg of the base polymer, the adjustment of the tensile modulus of the protective film, and the imparting of appropriate strength and rigidity to the protective film. The nitrogen atom-containing monomer may be used alone or in combination of two or more kinds.
[0046] The content of the nitrogen atom-containing monomer in the monomer component can be any suitable range. The content of the nitrogen atom-containing monomer in the monomer component can be, for example, 1% by weight or more, and from the viewpoint of obtaining a higher usage effect, it is preferably 3% by weight or more or 5% by weight or more, more preferably 10% by weight or more or 15% by weight or more, and may be 20% by weight or more, or may be 25% by weight or more. The content of the nitrogen atom-containing monomer in the monomer component may be, for example, less than 50% by weight, and from the viewpoint of the flexibility of the protective film, it is usually appropriate to be 40% by weight or less, may be 35% by weight or less, or may be 30% by weight or less.
[0047] The monomer components constituting the base polymer may contain one or more of the monomers exemplified above as well as any other appropriate monomer. Specific examples include carboxy group-containing monomers such as acrylic acid (AA), methacrylic acid (MAA), carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid; hydroxyl group (OH group)-containing monomers such as hydroxyalkyl (meth)acrylates and polypropylene glycol mono(meth)acrylates, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; maleic anhydride, anhydrous anhydride, and the like. Examples of functional group-containing monomers include acid anhydride group-containing monomers such as water itaconic acid; epoxy group-containing monomers such as glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, and allyl glycidyl ether; keto group-containing monomers such as diacetone (meth)acrylate, vinyl methyl ketone, vinyl ethyl ketone, allyl acetoacetate, and vinyl acetoacetate; alkoxysilyl group-containing monomers such as 3-(meth)acryloxypropyl trimethoxysilane, 3-(meth)acryloxypropyl triethoxysilane, 3-(meth)acryloxypropyl methyl dimethoxysilane, and 3-(meth)acryloxypropyl methyl diethoxysilane. The functional group-containing monomer can be useful for adjusting the properties such as the tensile modulus of elasticity of the protective film formed from the composition containing the polymer by imparting appropriate cohesiveness to the polymer. In addition, the SP value and Tg of the polymer can be adjusted to any appropriate range by selecting the type and amount of the functional group-containing monomer.
[0048] The monomer components constituting the base polymer (e.g., acrylic polymer) may contain other copolymerization components other than the functional group-containing monomers exemplified above for the purpose of improving cohesive strength, etc. Examples of such other copolymerization components include vinyl ester monomers such as vinyl acetate (VAc), vinyl propionate, and vinyl laurate; aromatic vinyl compounds such as styrene, substituted styrenes (α-methylstyrene, etc.), and vinyl toluene; cycloalkyl (meth)acrylates such as cyclohexyl (meth)acrylate, cyclopentyl (meth)acrylate, and isobornyl (meth)acrylate; aromatic vinyl compounds such as aryl (meth)acrylates (e.g., phenyl (meth)acrylate), aryloxyalkyl (meth)acrylates (e.g., phenoxyethyl (meth)acrylate), and arylalkyl (meth)acrylates (e.g., benzyl (meth)acrylate); olefin monomers such as ethylene, propylene, isoprene, butadiene, and isobutylene; chlorine atom-containing monomers such as vinyl chloride and vinylidene chloride; alkoxy group-containing monomers such as methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, and ethyl carbitol (meth)acrylate; vinyl ether monomers such as methyl vinyl ether and ethyl vinyl ether; and polyfunctional monomers having two or more (e.g., three or more) polymerizable functional groups (e.g., (meth)acryloyl groups) in one molecule, such as 1,6-hexanediol di(meth)acrylate and trimethylolpropane tri(meth)acrylate.
[0049] The other monomer components and other copolymerization components may be used in any appropriate content ratio. In some embodiments, the C 4-20 Alkyl (meth)acrylate, C 1-3 The total amount of the alkyl (meth)acrylate and the nitrogen atom-containing monomer may be, for example, 60% by weight or more, 70% by weight or more, 80% by weight or more, 85% by weight or more, or 90% by weight or more, or 95% by weight or more, 98% by weight or more, 99% by weight or more, or 99.5% by weight or more.
[0050] In some embodiments, the acid value of the base polymer (e.g., acrylic polymer) of the protective film is preferably 10 mg / KOH or less, more preferably 0 mg / KOH to 8 mg / KOH, even more preferably 0 mg / KOH to 5 mg / KOH, and particularly preferably 0 mg / KOH to 3 mg / KOH. The acid value of the base polymer is in the above range, which is preferable from the viewpoints of improving the peeling workability of the protective film (e.g., suppressing the occurrence of tearing or chipping), suppressing the occurrence of residues, improving productivity, etc. The acid value of the base polymer is measured in accordance with the potentiometric titration method specified in JIS K0070:1992.
[0051] In some embodiments of the technology disclosed herein, the SP value of the base polymer (e.g., acrylic polymer) of the protective film is, for example, 7 (cal / cm 3 ) 1 / 2 ~16(cal / cm 3 ) 1 / 2 In some preferred embodiments, the SP value is, for example, 9 (cal / cm 3 ) 1 / 2 ~14(cal / cm 3 ) 1 / 2 and more preferably 9 (cal / cm 3 ) 1 / 2 ~13(cal / cm 3 ) 1 / 2 and more preferably 9 (cal / cm 3 ) 1 / 2 ~12.5(cal / cm 3 ) 1 / 2 When the SP value is within the above range, better peelability is likely to be obtained. In this specification, the SP value refers to the value of the solubility parameter calculated from the basic structure of a compound by the method proposed by Fedors.
[0052] In the technology disclosed herein, the glass transition temperature (Tg) of the base polymer (e.g., acrylic polymer) of the protective film can be set to any appropriate value. The Tg of the base polymer may be, for example, about -60°C to 60°C, or about -50°C to 50°C. In some embodiments, the Tg of the base polymer is preferably -30°C to 30°C, more preferably -25°C to 25°C, and even more preferably -20°C to 20°C. When the Tg of the base polymer is in the above range, the protective film is easily adhered well to the surface of the object during the protection period of the object. For example, a protective film used to protect the circuit surface (which may be a surface having a plurality of bumps) of a semiconductor wafer having a circuit pattern tends to achieve better embedding properties.
[0053] In this specification, the glass transition temperature of the base polymer refers to a theoretical value calculated by the Fox formula based on the composition of the monomer components constituting each polymer. The theoretical glass transition temperature calculated by the Fox formula can be roughly consistent with the actual glass transition temperature calculated by a method such as differential scanning calorimetry (DSC) or dynamic viscoelasticity measurement. When the theoretical value cannot be calculated, the actual glass transition temperature can be used.
[0054] The Fox equation, as shown below, is a relational expression between the Tg of a copolymer and the glass transition temperature Tgi of a homopolymer obtained by homopolymerizing each of the monomers constituting the copolymer. 1 / Tg=Σ(Wi / Tgi) (In the formula, Tg represents the glass transition temperature (unit: K) of the copolymer, Wi represents the weight fraction of monomer i in the copolymer (copolymerization ratio on a weight basis), and Tgi represents the glass transition temperature (unit: K) of a homopolymer of monomer i.)
[0055] The glass transition temperature of the homopolymer used to calculate the calculated Tg can be a value described in a publicly known document. For example, for the monomers listed below, the following values are used as the glass transition temperatures of the homopolymers of the monomers. n-Butyl acrylate -55℃ Acrylonitrile 97℃ Vinyl acetate 32℃ Methyl methacrylate 105℃ Acrylic acid 106℃
[0056] For the glass transition temperature of homopolymers of monomers other than those exemplified above, the values described in "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989) can be used. When multiple values are described, the highest value is adopted. For monomers for which the glass transition temperature of homopolymers is not described in the Polymer Handbook, the value obtained by the measurement method described in JP-A-2007-51271 (actual glass transition temperature) can be used. Specifically, 100 parts by weight of monomer, 0.2 parts by weight of azobisisobutyronitrile, and 200 parts by weight of ethyl acetate as a polymerization solvent are charged into a reactor equipped with a thermometer, a stirrer, a nitrogen inlet tube, and a reflux condenser tube, and stirred for 1 hour while passing nitrogen gas through. After removing oxygen from the polymerization system in this way, the temperature is raised to 63°C and reacted for 10 hours. Then, the mixture is cooled to room temperature to obtain a homopolymer solution with a solid content concentration of 33% by weight. Next, this homopolymer solution is cast onto a release liner and dried to prepare a test sample (homopolymer sheet) with a thickness of about 2 mm. This test sample is punched out into a disk with a diameter of 7.9 mm, sandwiched between parallel plates, and the viscoelasticity is measured in a shear mode at a temperature range of -70°C to 150°C and a heating rate of 5°C / min while applying a shear strain of 1 Hz using a viscoelasticity tester (ARES, manufactured by Rheometrics). The peak top temperature of tan δ is taken as the Tg of the homopolymer.
[0057] The technology disclosed herein can be preferably applied to the peeling of a protective film formed from a composition for forming a protective film containing an aqueous emulsion of a base polymer (e.g., an acrylic polymer). The aqueous emulsion is obtained by emulsion polymerization of the monomer components as described above. The monomer supply method in the emulsion polymerization may be a batch-feed method in which all the monomer raw materials are supplied at once, a continuous supply (dropping) method, or a divided supply (dropping) method. In addition, a part or all of the monomer components may be mixed with water and an emulsifier in advance to be emulsified, and the emulsion may be supplied to the polymerization vessel.
[0058] The polymerization temperature can be set to any appropriate value depending on the types of monomers and solvents used, the type of polymerization initiator, etc. The polymerization temperature is, for example, 20° C. or higher, preferably 40° C. or higher, and more preferably 50° C. or higher. The polymerization temperature is preferably 95° C. or lower, and more preferably 85° C. or lower.
[0059] As the polymerization initiator, any appropriate initiator can be used. For example, an azo-based polymerization initiator, a peroxide-based initiator, a redox-based initiator formed by combining a peroxide with a reducing agent, a substituted ethane-based initiator, and the like can be mentioned. Specifically, 2,2'-azobisisobutyronitrile, 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine]hydrate, 2,2'-azobis(2-methylpropionamidine)disulfate, 2,2'-azobis(2-methylpropionamidine)dihydrochloride, 2,2'-azobis(2-methylpropionamidine)dihydrochloride, 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane]dihydrochloride, 2,2'-azobis(N, Azo initiators such as N'-dimethyleneisobutylamidine) dihydrochloride; persulfates such as potassium persulfate and ammonium persulfate; benzoyl peroxide, t-butyl hydroperoxide, di-t-butyl peroxide, dicumyl peroxide, dilauroyl peroxide, di-n-octanoyl peroxide, di(4-methylbenzoyl) peroxide, t-butyl peroxybenzoate, t-butyl peroxyisobutyrate, t-hexyl peroxypivalate, t-butyl peroxypivalate, di(2-ethylhexyl) peroxydicarbonate, di(4-t-butylcyclohexyl) peroxydicarbonate, di-sec-butyl peroxy Examples of the initiator include peroxide initiators such as dicarbonate, t-butylperoxyneodecanoate, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)cyclododecane, 1,1-bis(t-hexylperoxy)cyclohexane, and hydrogen peroxide; and redox initiators such as a combination of a peroxide and ascorbic acid (for example, a combination of aqueous hydrogen peroxide and ascorbic acid), a combination of a peroxide and an iron (II) salt (for example, a combination of aqueous hydrogen peroxide and an iron (II) salt), a combination of a persulfate and a hydrogen sulfite, and a combination of a persulfate and a metabisulfite.
[0060] The polymerization initiator is used in any appropriate amount. For example, the amount of the polymerization initiator used relative to 100 parts by weight of the monomer component is preferably 0.001 to 5 parts by weight, more preferably 0.01 to 3 parts by weight, and further preferably 0.01 to 2 parts by weight.
[0061] Emulsion polymerization is usually carried out in the presence of an emulsifier. Any suitable emulsifier can be used as the emulsifier, such as an anionic emulsifier, a nonionic emulsifier, etc. The emulsifier may be used alone or in combination of two or more kinds.
[0062] Examples of anionic emulsifiers include sodium lauryl sulfate, ammonium lauryl sulfate, sodium dodecylbenzenesulfonate, sodium polyoxyethylene lauryl sulfate, sodium polyoxyethylene alkyl ether sulfate, ammonium polyoxyethylene alkyl phenyl ether sulfate, sodium polyoxyethylene alkyl phenyl ether sulfate, sodium polyoxyethylene alkyl sulfosuccinate, etc. Examples of nonionic emulsifiers include polyoxyethylene alkyl ether, polyoxyethylene alkyl phenyl ether, polyoxyethylene fatty acid ester, polyoxyethylene polyoxypropylene block polymer, etc. In addition, an emulsifier having a reactive functional group (reactive emulsifier) may be used as the emulsifier. Examples of reactive emulsifiers include radical polymerizable emulsifiers having a structure in which a radical polymerizable functional group such as a propenyl group or an allyl ether group is introduced into the above anionic emulsifier or nonionic emulsifier.
[0063] The emulsifier is used in any suitable amount.In some embodiments, the amount of emulsifier used relative to the total of 100 parts by weight of monomer components may be, for example, 0.05 parts by weight or more or 0.1 parts by weight or more, preferably 0.2 parts by weight or more, more preferably 0.5 parts by weight or more, even more preferably 1.0 parts by weight or more, and particularly preferably 1.5 parts by weight or more.In addition, from the viewpoint of suppressing foaming during emulsion polymerization and the composition containing the obtained emulsion, the amount of emulsifier used is usually preferably 10 parts by weight or less, more preferably 5 parts by weight or less, and even more preferably 3 parts by weight or less relative to the total of 100 parts by weight of monomer components.
[0064] The emulsion polymerization may be carried out in the presence of a protective colloid. Examples of the protective colloid include polyvinyl alcohol-based polymers such as partially saponified polyvinyl alcohol, fully saponified polyvinyl alcohol, and modified polyvinyl alcohol; cellulose derivatives such as hydroxyethyl cellulose, hydroxypropyl cellulose, and carboxymethyl cellulose salt; and natural polysaccharides such as guar gum. Only one type of protective colloid may be used, or two or more types may be used in combination.
[0065] The degree of saponification of the partially saponified polyvinyl alcohol is typically 98 mol% or less (for example, less than 98 mol%), and may be less than 97.8 mol%, less than 95 mol%, less than 92 mol%, or less than 90 mol% or less. From the viewpoint of emulsion stability and the like, the degree of saponification of the partially saponified polyvinyl alcohol is preferably 65 mol% or more, more preferably 70 mol% or more, even more preferably 80 mol% or more, and particularly preferably 85 mol% or more. Note that polyvinyl alcohol having a degree of saponification in the range of 90 mol% or more (for example, more than 90 mol%) and 98 mol% or less is sometimes referred to as intermediate saponification type polyvinyl alcohol. In addition, the polyvinyl alcohol may be a fully saponified polyvinyl alcohol (typically, a polyvinyl alcohol having a degree of saponification of about 98.0 mol% or more) as described above.
[0066] Examples of modified polyvinyl alcohol include anion-modified polyvinyl alcohol into which an anionic group such as a carboxyl group and / or a sulfonic acid group has been introduced; and cation-modified polyvinyl alcohol into which a cationic group such as a quaternary ammonium salt has been introduced. The degree of saponification of the modified polyvinyl alcohol is, for example, less than 98 mol%, preferably less than 95 mol%, more preferably less than 92 mol%, and even more preferably less than 90 mol%. The degree of saponification of the modified polyvinyl alcohol is, for example, 55 mol% or more, and from the viewpoint of the stability of the emulsion, it is preferably 65 mol% or more, more preferably 70 mol% or more, even more preferably 80 mol% or more, and particularly preferably 85 mol% or more.
[0067] The protective colloid is used in any suitable amount. The amount of the protective colloid used is preferably 0.1 parts by weight or more, more preferably 0.5 parts by weight or more, and even more preferably 0.7 parts by weight or more, based on 100 parts by weight of the total of the monomer components. The amount of the protective colloid used is preferably 10 parts by weight or less, more preferably 5 parts by weight or less, even more preferably 3 parts by weight or less, and particularly preferably 2 parts by weight or less, based on 100 parts by weight of the total of the monomer components. The protective colloid may be used in combination with the emulsifier, or only the protective colloid may be used without using an emulsifier. Preferably, the emulsifier and the protective colloid are used in combination. For example, emulsion polymerization can be performed in such a manner that water and a protective colloid are placed in a polymerization vessel, and a part or all of the monomer composition is mixed with water and an emulsifier in advance to emulsify the resulting emulsion, which is then supplied to the polymerization vessel. When an anionic protective colloid (e.g., anionically modified polyvinyl alcohol) is used in combination with an emulsifier, it is preferable to use at least one emulsifier selected from the group consisting of anionic emulsifiers and nonionic emulsifiers, from the viewpoint of polymerization stability, etc.
[0068] Any suitable chain transfer agent may be used during polymerization. Examples of the chain transfer agent include mercaptans such as n-dodecyl mercaptan, t-dodecyl mercaptan, and thioglycolic acid. Chain transfer agents that do not contain sulfur atoms (non-sulfur chain transfer agents) may also be used. Specific examples of non-sulfur chain transfer agents include anilines such as N,N-dimethylaniline and N,N-diethylaniline; terpenoids such as α-pinene and terpinolene; styrenes such as α-methylstyrene and α-methylstyrene dimer; compounds having a benzylidenyl group such as dibenzylideneacetone, cinnamyl alcohol, and cinnamyl aldehyde; hydroquinones such as hydroquinone and naphthohydroquinone; quinones such as benzoquinone and naphthoquinone; olefins such as 2,3-dimethyl-2-butene and 1,5-cyclooctadiene; alcohols such as phenol, benzyl alcohol, and allyl alcohol; benzyl hydrogens such as diphenylbenzene and triphenylbenzene; and the like. The chain transfer agent may be used alone or in combination of two or more. When a chain transfer agent is used, the amount of the chain transfer agent used may be, for example, about 0.01 to 1 part by weight based on 100 parts by weight of the total of the monomer components.
[0069] The protective film forming composition may further contain any suitable additive as necessary. Examples of the additive include water-soluble polymers (water-soluble polymers added after emulsion polymerization separately from protective colloids that may be used during emulsion polymerization), surfactants (surfactants added after emulsion polymerization separately from emulsifiers that may be used during emulsion polymerization), rust inhibitors, plasticizers, softeners, flame retardants, tackifiers, conductive materials, catalysts (e.g., platinum catalysts), flow regulators such as thickeners and thixotropic agents, solvents, leveling agents, film-forming assistants, peeling regulators, colorants such as pigments and dyes, fillers, ultraviolet absorbers, light stabilizers, anti-aging agents, preservatives, and defoamers. The additives are used in any suitable amount depending on the purpose.
[0070] The composition for forming a protective film can be produced by any suitable method. For example, a base polymer (e.g., an acrylic polymer) and any additives may be added to any suitable solvent and mixed, or any additives may be added to an aqueous emulsion (polymerization reaction liquid) obtained by emulsion polymerization of a base polymer (e.g., an acrylic polymer) and mixed. The aqueous emulsion may be used as it is, or the pH may be adjusted to about 6 to 8 by adding, for example, aqueous ammonia to the aqueous emulsion, or the solid content concentration may be adjusted by adding any suitable solvent, and the like, and used as the composition for forming a protective film.
[0071] As the solvent, any appropriate solvent can be used. An aqueous solvent is preferably used. In this specification, an aqueous solvent refers to water or a mixed solvent containing water as the main component (a component contained in excess of 50% by weight). As the solvent other than water constituting this mixed solvent, an organic solvent that can be mixed uniformly with water (for example, a lower alcohol having about 1 to 3 carbon atoms, etc.) can be used. The organic solvent that can be mixed uniformly with water may be used alone or in combination of two or more kinds. The proportion of water in the aqueous solvent is, for example, 90% by weight or more, and preferably 95% by weight to 100% by weight.
[0072] The BH viscosity of the protective film-forming composition is not particularly limited, and can be appropriately set in consideration of, for example, the coating method and coating device of the protective film-forming composition during the formation of the protective film (film formation), the coating speed, coating thickness, the material of the surface to which the composition is applied, the surface shape, and the attitude (for example, the degree of inclination with respect to a horizontal plane). The BH viscosity of the protective film-forming composition can be, for example, within a range of about 0.01 Pa·s to 1000 Pa·s. In some embodiments, the BH viscosity may be, for example, about 0.1 Pa·s to 10 Pa·s, preferably 0.2 Pa·s to 5 Pa·s, more preferably 0.3 Pa·s to 3 Pa·s, and even more preferably 0.5 Pa·s to 2 Pa·s. In some other embodiments, the BH viscosity may be, for example, about 1 Pa·s to 500 Pa·s, preferably 10 Pa·s to 300 Pa·s, more preferably 20 Pa·s to 200 Pa·s, and even more preferably 40 Pa·s to 100 Pa·s. In this specification, the BH viscosity refers to the viscosity measured by a BH type viscometer at 30° C. and 2 rpm. Any appropriate rotor can be used for the measurement depending on the viscosity, and for example, a No. 2 rotor can be used.
[0073] The thickness of the protective film is set to any appropriate value. For example, the thickness can be set according to the surface shape of the target surface on which the protective film is formed, the degree of protective function required, and the like. Although not particularly limited, the thickness of the protective film can be, for example, 10 μm or more, 20 μm or more, 50 μm or more, 70 μm or more, or 100 μm or more, and can be, for example, 1000 μm or less, 500 μm or less, 300 μm or less, 200 μm or less, or 150 μm or less. It is advantageous from the viewpoint of protectiveness and leveling properties that the thickness of the protective film is not too small. It is advantageous from the viewpoint of ease of film formation (for example, prevention of foaming during drying) and suppression of sagging.
[0074] In some embodiments, the protective film suitably has a water absorption rate of 1% or more based on the water absorption rate measurement described below. [Water absorption measurement] A sample having the above protective film provided on the surface of a flat glass plate is immersed in ion-exchanged water at 23° C. for 30 minutes, and the water absorption is calculated from the weight W0 of the above protective film before immersion and the weight W1 after immersion according to the following formula. Water absorption rate [%]=(W1-W0) / W0×100
[0075] By the protective film having a certain degree of water absorption, for example, even in the case where water is mainly supplied from the back surface of the protective film in the water supply-freezing treatment or mainly from the end surface (typically the outer peripheral end surface) of the protective film, the supplied water can reach the interface with the object or its vicinity, and the peeling force reduction effect by the water supply-freezing treatment can be appropriately exhibited. In some embodiments, the water absorption rate is advantageously 2% or more, preferably 3% or more (e.g., more than 3%), more preferably 4% or more, and may be 5% or more, 6% or more, or 7% or more. In some embodiments, the water absorption rate is suitably, for example, 50% or less, preferably 40% or less, more preferably 30% or less or 25% or less, may be 20% or less, may be 15% or less, or may be 12% or less. For example, a water absorption rate that is not too high can be advantageous in terms of the water resistance (water-resistant protection) of the protective film during the protection period, the prevention of tearing or deformation of the protective film during the peeling operation after the water supply-freezing treatment, the prevention of the generation of residue, and the like.
[0076] Although not particularly limited, the tensile modulus of the protective film at 23°C (hereinafter, sometimes referred to as "tensile modulus (23°C)") may be, for example, approximately 5 GPa or less, and is usually suitably 4 GPa or less, and is preferably 3 GPa or less, 2.5 GPa or less, or 2.0 GPa or less, and more preferably 1.5 GPa or less, 1.3 GPa or less, and may be 1.1 GPa or less, 1.0 GPa or less, or may be 0.95 GPa or less. It may be advantageous in terms of adhesion to the surface of the object to be protected during the protection period if the tensile modulus of the protective film (23°C) is not too high. In some embodiments, the tensile modulus of the protective film (23°C) may be, for example, 800 MPa or less, 500 MPa or less, 200 MPa or less, 100 MPa or less, or 50 MPa or less. The peeling method disclosed herein includes a water supply-freezing treatment step, and can therefore be effective in significantly improving the peelability of a protective film even when applied to such a protective film having a relatively low tensile modulus (23°C).
[0077] Although not particularly limited, the tensile modulus (23°C) of the protective film may be, for example, 1 MPa or more or 5 MPa or more. In some embodiments, the tensile modulus (23°C) is preferably 10 MPa or more, more preferably 20 MPa or more or 40 MPa or more, and may be 60 MPa or more, or may be 80 MPa or more. For example, in an embodiment in which a processing step of an object is performed in a form in which no other layer (e.g., a base layer) is present on the back side of the protective film, the tensile modulus (23°C) of the protective film is not too low, which can be advantageous from the viewpoint of enhancing the protective function of the protective film. In some preferred embodiments, the tensile modulus (23°C) of the protective film may be, for example, 0.1 GPa or more, 0.15 GPa or more, 0.2 GPa or more, 0.3 GPa or more, 0.4 GPa or more, or 0.5 GPa or more.
[0078] In this specification, the tensile modulus (23°C) of a protective film refers to a value measured by the following method. That is, the protective film (film) to be measured (for example, a film formed to a thickness of about 100 μm) is cut to a size of 100 mm in length and 25 mm in width, and pulled using a precision universal testing machine (manufactured by Shimadzu Corporation, device name "Autograph AG-IS") with a chuck distance of 50 mm and a pulling speed of 300 mm / min, and the change in stress until the film is plastically deformed is recorded to obtain a stress-strain curve. The tensile modulus is the strain ε at two specified points. 1 = 1 and ε 2 The tensile modulus is determined by linear regression of the curve between =2. The above measurements are performed using three test pieces cut out from different locations, and the average value is the tensile modulus. The above measurements are performed in accordance with JIS K7161, under an environment of 23°C and 50% RH.
[0079] The protective film in the technology disclosed herein may be used in an embodiment having a substrate layer on the back surface of the protective film. Examples of the substrate layer include various resin films, rubber sheets, foam sheets, metal foils, fiber aggregates, and composites thereof. The concept of the fiber aggregate includes paper (e.g., Japanese paper, craft paper, glassine paper, fine paper, synthetic paper, topcoat paper, etc.), nonwoven fabric, woven fabric (which may be an inorganic woven fabric such as glass cloth), knitted fabric, etc. In some embodiments, from the viewpoint of efficiently supplying moisture to the protective layer, it is preferable that the substrate layer has moisture (water and / or water vapor) permeability or has a property of being able to retain moisture. In addition, the protective film in the technology disclosed herein may be used in an embodiment in which a single-sided pressure-sensitive adhesive sheet with a substrate is attached to the back surface of the protective film.
[0080] In the technology disclosed herein, the protective film covering the surface of the object may be, for example, a liquid composition (composition for forming a protective film) applied to the object and dried to form (form a film) on the object, or may be a protective film formed (formed) in advance and coated on the object. When forming a protective film prior to coating the object, for example, a method of forming a protective film by applying a composition for forming a protective film to a sheet having peelability (for example, release paper, release film, etc.) to form a protective film, and then pressing (transferring) the protective film on the release sheet to the object to coat it, and then removing the release sheet, or a method of applying a composition for forming a protective film to a substrate layer (for example, a resin film) to form a protective film, pressing the protective film on the release sheet to the object, and coating the protective film on the object in a form having the substrate layer on the back side, etc., can be used to cover the surface of the object with a protective film.
[0081] The object protected by the protective film may be, for example, but is not limited to, a surface of a semiconductor substrate, a surface of a glass substrate, a surface of an electronic component, a surface of a prism sheet, etc. The peeling method disclosed herein may be preferably applied to peeling off a protective layer covering a surface of a semiconductor wafer on which a circuit pattern (for example, circuit components such as bumps) is formed.
[0082] The surface of the object may be, for example, a flat surface (for example, a smooth flat surface), a curved surface, a surface having steps or irregularities, a surface having a composite structure of these, etc. The peeling method disclosed herein may be implemented, for example, in an embodiment in which the surface of the object has a plurality of irregularities (a surface with a large surface roughness), and may suitably exhibit the peeling force reduction effect by the freezing treatment after the water supply. The reason for this is not particularly limited, but according to the peeling method disclosed herein, the water present at or near the interface between the protective film and the object freezes and expands in volume due to the freezing treatment after the water supply, which pushes the protective film up from the object surface, and the engagement between the inner surface of the protective film (the surface facing the object) and the irregularities on the object surface is released, which is thought to effectively reduce the peeling force of the protective layer.
[0083] <Semiconductor wafer processing method> According to this specification, a method for processing a semiconductor wafer is provided by utilizing any of the peeling methods disclosed herein. The processing method includes, for example, covering a surface of a semiconductor wafer on which a circuit pattern (for example, circuit components such as bumps, wiring, etc.) is formed with a protective film containing a resin material; processing (for example, grinding) a surface of the semiconductor wafer that is not covered with the protective film; supplying water to the protective film and then performing a freezing treatment; and peeling and removing the protective film that has been subjected to the freezing treatment. The processing (grinding) step may be performed while supplying water to the processing surface for the purpose of cooling the grinding part, suppressing scattering of grinding debris, etc. The supply of water to the protective film may be performed by the water being absorbed into the protective film during the processing step. In other words, the execution of the processing step may also serve as the supply of water to the protective film.
[0084] 2A, 2B, and 2C are cross-sectional views each showing a typical step of the semiconductor wafer processing method according to one embodiment of the present invention. Each step will be described below in order. First, the surface of the semiconductor wafer 200 on which the circuit pattern (e.g., bumps) is formed is covered with a protective film 100 (FIG. 2(a)). In this embodiment, the protective film 100 is formed, for example, by applying a liquid composition for forming a protective film (preferably a composition in the form of an aqueous emulsion) to the semiconductor wafer 200 so as to fill the protruding parts of the bumps, and then drying the composition. The liquid composition for forming a protective film generally has excellent embedding properties for the semiconductor wafer surface. Therefore, even on the surface of a semiconductor wafer with high protruding bumps or a semiconductor wafer on which bumps are densely formed, the protective film can satisfactorily fill in the spaces between the bumps.
[0085] Examples of the coating method include spin coat coating, RS coater coating, spray coating, ribbon coating, curtain coating, roller coating, brush coating, bar coater coating, air knife coating, gravure coating, gravure reverse coating, reverse roll coating, lip coating, die coating, dip coating, offset printing, flexographic printing, and screen printing. Preferably, spin coat coating, RS coater coating, spray coating, or curtain coating is used. By using these methods, the embedding ability of the unevenness on the semiconductor wafer surface can be further improved.
[0086] Any appropriate method can be used as the drying method. For example, natural drying, air drying, reduced pressure drying, heat drying, etc. can be mentioned. Heat drying is preferably used. When heat drying is performed, the heating temperature is, for example, 30° C. to 100° C. The drying time is, for example, 1 minute to 60 minutes.
[0087] After forming the protective film 100 as shown in FIG. 2(a), a single-sided adhesive sheet with a substrate having an adhesive layer on one side of the substrate layer may be attached so that the adhesive layer is in contact with the back surface of the protective film 100 (the surface opposite the semiconductor wafer 200).
[0088] The back grinding of the semiconductor wafer can be performed by any suitable method (FIG. 2(b)). The back grinding is performed on the surface of the semiconductor wafer on which no circuit is formed (the surface of the semiconductor wafer on which no protective film is formed). The back grinding is generally performed while cooling with water. As described above, the protective film formed using the liquid surface protective material has excellent embedding properties. Therefore, it is possible to appropriately prevent water from penetrating between the semiconductor wafer and the protective film during back grinding. In addition, by performing the back grinding while cooling with water in this manner, the water is supplied to the exposed surface (end face, back face, etc.) of the protective film and is absorbed by the protective film.
[0089] After the back surface grinding, the semiconductor wafer 100 having the protective film 200 to which the water has been supplied is subjected to a freezing process to reduce the peeling force of the protective film 200 from the semiconductor wafer 100. This allows the protective film 200 to be satisfactorily peeled and removed from the semiconductor wafer 100 (FIG. 2(c)).
[0090] As will be understood from the above description and the examples described below, the matters disclosed in this specification include the following. [1] A method for peeling off a protective film covering a surface of an object from the object, wherein the protective film is a film containing a resin material, The method includes supplying water to the protective film and then performing a freezing treatment. [2] The peeling method according to the above [1], wherein the protective film is a film formed from a water-dispersible resin composition. [3] The peeling method according to [1] or [2] above, wherein the protective film has a water absorption rate of more than 3% based on the water absorption rate measurement described below. [Water absorption measurement] A sample having the above protective film provided on the surface of a flat glass plate is immersed in ion-exchanged water at 23° C. for 30 minutes, and the water absorption is calculated from the weight W0 of the above protective film before immersion and the weight W1 after immersion according to the following formula. Water absorption rate [%]=(W1-W0) / W0×100 [4] The peeling method according to any one of the above [1] to [3], wherein the protective film has a tensile modulus of elasticity of 10 MPa or more at 23°C. [5] The peeling method according to any one of [1] to [4] above, wherein the surface of the object has a plurality of projections and recesses. [6] The peeling method according to any one of [1] to [5] above, wherein the surface of the object is a surface of a semiconductor wafer on which a circuit pattern is formed. [7] Covering the surface of a semiconductor wafer on which a circuit pattern is formed with a protective film containing a resin material; grinding a surface of the semiconductor wafer not covered with the protective film; providing water to the protective film and then subjecting it to a freezing treatment; and peeling and removing the protective film that has been subjected to the freezing treatment; A method for processing a semiconductor wafer, comprising: EXAMPLES
[0091] Below, several experimental examples related to the present invention will be described, but it is not intended that the present invention be limited to those specific examples. In the following description, "parts" and "%" representing the amount used or the content are based on weight unless otherwise specified. In addition, unless otherwise specified, the amount of each material used is based on the amount of active ingredient.
[0092] <Experimental Example 1> <Preparation of Resin Composition> (Composition A) 25 parts of ion-exchanged water was placed in a container, and 100 parts of monomer components consisting of 66.4 parts of n-butyl acrylate (BA) and 33.6 parts of acrylonitrile (AN) were added to a surfactant solution in which 2 parts of polyoxyalkylene alkenyl ether (manufactured by Kao Corporation, product name "Latemul PD-420") and 0.5 parts of sodium dodecylbenzenesulfonate (manufactured by Kao Corporation, product name "Neopelex G-65") were dissolved, and the mixture was emulsified using an emulsifier (homomixer) to prepare a monomer emulsion. In a reaction vessel equipped with a cooling tube, a nitrogen inlet tube, a thermometer, and a stirrer, 75 parts of ion-exchanged water was placed, and 2.0 parts of anion-modified polyvinyl alcohol (manufactured by Mitsubishi Chemical Corporation, trade name "Gosenex L-3266"; saponification degree 86.5 to 89.0 mol%) was added, dissolved while introducing nitrogen gas, and heated to 70°C. The above monomer emulsion (containing 100 parts of monomer component), 0.3 parts of sodium metabisulfite aqueous solution (based on solid content), and 0.3 parts of ammonium persulfate aqueous solution (based on solid content) were added thereto over a period of 5 hours while maintaining the system at approximately 70°C, and an emulsion polymerization reaction was carried out. After the addition was completed, the same temperature was maintained for another 3 hours for aging. The resulting reaction mixture was cooled to room temperature, and the pH was adjusted to 7.5 by adding 10% ammonium water, and acrylic polymer P was obtained. A The aqueous emulsion (solid content: about 47%) was used as composition A. AThe Tg of is -20.1°C and the SP value is 11.8 (cal / cm 3 ) 1 / 2 It is.
[0093] (Composition B) The composition A is added with the acrylic polymer P contained in the composition A. A To 100 parts of the mixture, 1.5 parts (based on solid content) of polyoxyethylene alkyl ether (manufactured by Kao Corporation, product name "EMULGEN 1135S-70") was added, and the mixture was stirred and mixed uniformly to prepare composition B.
[0094] <Removability evaluation> Comparative Example 1 The above composition A was applied to the bump-formed surface (circuit surface) of a silicon wafer (wafer diameter 8 inches, thickness 715 μm; bump height 75 μm, diameter 90 μm, pitch 150 μm; hereinafter also referred to as "bump wafer") with Sn-Ag alloy bumps formed on one side, to a width of 20 mm and a thickness of 200 μm, and dried at 80° C. for 3 minutes to form a protective film with a thickness of about 100 μm. This was used as a sample for peeling test. The above sample was set in a tensile tester in a standard environment of 23°C and 50% RH, and a 180° peel test was performed using the tensile tester at a tensile speed of 300 mm / min. The initial peel strength F of the protective film formed from composition A was measured. 0 was measured.
[0095] Comparative Example 2 A sample prepared in the same manner as in Comparative Example 1 was immersed in ion-exchanged water at 23° C. for 10 minutes (water supply treatment). The sample was taken out of the ion-exchanged water, the adhering water was lightly wiped off, and the sample was allowed to stand for 1 minute in the above-mentioned standard environment, after which a 180° peel test was carried out at a tensile speed of 300 mm / min, and the peel force (peel force after water supply treatment F W ) was measured.
[0096] Comparative Example 3 A sample prepared in the same manner as in Comparative Example 1 was left to stand for 20 minutes in a low-temperature room maintained at an environment of -5°C (freezing treatment). The sample was then removed from the low-temperature room and left to stand for 1 minute in the above-mentioned standard environment, after which a 180° peel test was carried out at a tensile speed of 300 mm / min to measure the peel force (peel force after freezing treatment F F ) was measured.
[0097] Example 1 A sample prepared in the same manner as in Comparative Example 1 was immersed in ion-exchanged water at 23°C for 10 minutes (water supply treatment). The sample was taken out of the ion-exchanged water, the adhering water was lightly wiped off, and then the sample was left to stand in a low-temperature room maintained at an environment of -5°C for 20 minutes (freezing treatment). Next, the sample was taken out of the low-temperature room and left to stand in the above-mentioned standard environment for 1 minute, after which a 180° peel test was carried out at a tensile speed of 300 mm / min, and the peel force (peel force after water supply-freezing treatment F WF ) was measured.
[0098] Comparative Example 4 The initial peel strength F of the protective film formed from composition B was measured in the same manner as in Comparative Example 1, except that composition B was used instead of composition A. 0 was measured.
[0099] Example 2 The peel strength (F after the water supply treatment and the freezing treatment) was measured in the same manner as in Example 1, except that the composition B was used instead of the composition A. WF ) was measured.
[0100] The results are shown in Table 1. Table 1 also shows the initial peel strength F of the protective film formed from composition A. 0 The reduction rate of each peel strength when the protective film was peeled off by the methods of Comparative Examples 2, 3 and Example 1, compared to Comparative Example 1, and the initial peel strength F of the protective film formed from Composition B 0 The reduction rate of peeling force when the protective film was peeled off by the method of Example 2 relative to (Comparative Example 4) is also shown.
[0101] [Table 1]
[0102] As shown in Table 1, in peeling the protective film formed from composition A, the peeling method of Example 1, in which a water supply-freezing treatment was performed, was clearly more effective in reducing the initial peeling force (the peeling force of Comparative Example 1) than Comparative Examples 2 and 3, in which only one of the water supply treatment and the freezing treatment was performed. Similarly, in peeling the protective film formed from composition B, Example 2, in which a water supply-freezing treatment was performed, was found to have a significant effect of reducing the initial peeling force (the peeling force of Comparative Example 4).
[0103] <Experimental Example 2> <Preparation of Resin Composition> (Composition C) 61.4 parts of BA, 19.9 parts of AN, 18.7 parts of methyl methacrylate (MMA), 0.05 parts of n-lauryl mercaptan, 2 parts of sodium polyoxyethylene lauryl sulfate (Kao Corporation, product name "Latemul E118B"), and 40 parts of ion-exchanged water were mixed and emulsified in an emulsifier (homomixer) while replacing with nitrogen to prepare a monomer emulsion. In a reaction vessel equipped with a cooling tube, a nitrogen inlet tube, a thermometer and a stirrer, 50 parts of ion-exchanged water was placed, 1.0 part of anion-modified polyvinyl alcohol (manufactured by Mitsubishi Chemical Corporation, trade name "Gosenex L-3266") was added, and dissolved at room temperature while introducing nitrogen gas. The temperature was raised to 60°C, and 0.1 part of 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine]hydrate (Wako Pure Chemical Industries, Ltd., trade name "VA-057") was added as a polymerization initiator. While maintaining the system at around 60°C, the above monomer emulsion was added over 3 hours to carry out a polymerization reaction. After the addition of the monomer emulsion was completed, the mixture was kept at the same temperature for another 3 hours to mature. The resulting reaction mixture was cooled to room temperature, and then the pH was adjusted to 7.5 by adding 10% ammonium water to obtain acrylic polymer P. C This aqueous emulsion was used as composition C. The acrylic polymer P C The Tg of is -13.1°C and the SP value is 10.9 (cal / cm 3 ) 1 / 2 It is.
[0104] (Composition D) The emulsion polymerization was carried out without using anion-modified polyvinyl alcohol (manufactured by Mitsubishi Chemical Corporation, product name "Gohsenex L-3266"), but the acrylic polymer P in composition C was C In the same manner as in the preparation of the aqueous emulsion of acrylic polymer P D The aqueous emulsion of the acrylic polymer P was obtained. D Aqueous emulsion of acrylic polymer P D Composition D was prepared by adding 2.0 parts of polyvinyl alcohol (manufactured by Japan Vinyl Acetate & Poval Co., Ltd., product name "JT-05"; saponification degree 93.5 to 95.0 mol % (intermediate saponification type)) per 100 parts of the mixture and stirring uniformly.
[0105] (Composition E) The acrylic polymer P D Aqueous emulsion of acrylic polymer P D Composition E was prepared by adding 2.0 parts of polyvinyl alcohol (manufactured by Japan Vinyl Acetate & Poval Co., Ltd., product name "JL-18E"; saponification degree 83.0 to 86.0 mol % (partially saponified type)) per 100 parts of the mixture and uniformly mixing with stirring.
[0106] (Composition F) Composition F is an acrylic polymer P D The aqueous emulsion was used as is.
[0107] <Removability evaluation> Example 3 The above composition C was applied in a width of 20 mm on the bump formation surface (circuit surface) of the same bump wafer as used in Experimental Example 1, and dried at 80° C. for 3 minutes to form a protective film with a thickness of about 100 μm. This was used as a sample for evaluating peelability. The above sample was immersed in ion-exchanged water at 23°C for 10 minutes (water supply treatment). The sample was removed from the ion-exchanged water, and the adhering water was lightly wiped off, and then the sample was left to stand in a low-temperature room maintained at an environment of -5°C for 20 minutes (freezing treatment). Next, the sample was removed from the low-temperature room and left in a standard environment of 23°C and 50% RH for about 1 minute. Then, one end of the protective film in the longitudinal direction of the sample was peeled off from the wafer surface, and the peeled part was grabbed by hand and peeled off from the circuit surface, to evaluate the peelability of the protective film after the water supply-freezing treatment (post-treatment peelability). In addition, for the sample before the above-mentioned water supply treatment, one end of the protective film in the longitudinal direction of the sample was peeled off from the wafer surface, and the peeled part was grasped with the hand and pulled off from the circuit surface to evaluate the initial peelability of the protective film. Comparing the post-treatment peelability with the initial peelability, if the water supply-freezing treatment showed a slight improvement in the peelability of the protective film, the treatment effect was rated as "fair", if a clear improvement was observed, it was rated as "good", and if a significant improvement was observed, it was rated as "excellent".
[0108] (Examples 4 to 6) The treatment effect was evaluated by comparing the post-treatment releasability and initial releasability of the protective film of each example in the same manner as in Example 3, except that compositions D to F were used instead of composition C.
[0109] <Water absorption rate measurement> The weight of a flat glass plate (alkali glass plate manufactured by Matsunami Glass Industry Co., Ltd., thickness 1.35 mm, blue plate edge polished product) was measured. The above compositions A, C to F were each applied to one side of the above glass plate and dried at 80°C for 1 hour to form a protective film with a thickness of about 100 μm. The weight of the above glass plate with protective film was measured, and the weight of the above glass plate alone was subtracted therefrom to calculate the dry weight of the protective film (weight before immersion; W0). The above glass plate with protective film was immersed in ion-exchanged water at 23°C for 30 minutes, then removed from the ion-exchanged water, and the surface moisture was lightly wiped off, and the weight of the above glass plate with protective film was measured. The weight of the protective film after immersion (W1) was calculated by subtracting the weight of the above glass plate alone from the measured value obtained. The water absorption rate of the protective film was calculated from the above weight before immersion W0 and the above weight after immersion according to the following formula. Water absorption rate [%]=(W1-W0) / W0×100
[0110] The results obtained are shown in Table 2, together with the results of a similar evaluation carried out on composition A used in Example 1.
[0111] [Table 2]
[0112] As can be seen from the results of Examples 3 to 6 shown in Table 2, by subjecting the protective films formed from compositions C to F to a water supply-freezing treatment, an effect of improving the initial peelability of the protective film was observed, similar to the case of subjecting the protective film formed from composition A to a water supply-freezing treatment. Compared with the protective film formed from composition F (water absorption 3%), the protective films formed from compositions A and C to E (water absorption 5% or more) showed a higher peelability improving effect. In addition, when the protective films formed from compositions C to F were subjected to a water supply-freezing treatment and peeled off, the peel force, in descending order (in descending order of severity of peeling), was Example 6>>Examples 3 and 5>Example 4.
[0113] <Experimental Example 3> (Examples 7 to 11) Instead of the composition of Example 3, in Example 7, a composition G was prepared by blending a film-forming aid with a commercially available emulsion-type polyurethane resin composition (manufactured by Sanyo Chemical Industries, Ltd., product name "Permarin UA-368"); in Example 8, a composition H was prepared by blending a film-forming aid with a commercially available acrylonitrile-butadiene-based latex (manufactured by Nippon Zeon Co., Ltd., product name "Nipol 1551"); in Example 9, a composition I was prepared by blending a film-forming aid with a commercially available styrene-butadiene-based latex (manufactured by JSR Corporation, product name "2527A"); in Example 10, a composition J was prepared by blending a film-forming aid with a commercially available ethylene-vinyl acetate copolymer emulsion (manufactured by Wacker, product name "VINNAPAS EP 724"); and in Example 11, a commercially available polyester-acrylic resin emulsion (manufactured by Resonac, product name "Polysol"). A protective film having a thickness of about 100 μm was formed on the bump formation surface (circuit surface) of the bump wafer in the same manner as in Example 3, except that composition K prepared by mixing a film-forming assistant with "FP-3000A" was used. This was used as a sample for evaluating peelability. Dipropylene glycol n-butyl ether (manufactured by The Dow Chemical Company, product name "Dowanol DPnB") was used as the film-forming assistant in all of compositions G to K. The amount of film-forming assistant used was 0.25 to 0.27 parts per 50 parts of polymer.
[0114] The samples according to each Example were compared in terms of releasability after water supply-freezing treatment and initial releasability in the same manner as in Example 3. As a result, the releasability of the protective films according to Examples 7 to 11 was improved by subjecting them to water supply-freezing treatment. In addition, in a comparison of the releasability after water supply-freezing treatment between the protective films formed from each composition, the protective films formed from compositions G, H, and I had particularly good releasability. In addition, the protective films formed from compositions I and J had relatively low water-resistant protective properties or strength of the protective film when absorbing water, compared to the other protective films.
[0115] The water absorption of the protective films formed from each of compositions G to J was measured in the same manner as in the water absorption measurement of Experimental Example 2. The water absorption of each protective film was 5% for the protective film formed from composition G, 5% for the protective film formed from composition H, 22% for the protective film formed from composition I, 41% for the protective film formed from composition J, and 3% for the protective film formed from composition K.
[0116] Example 12 In this example, the protective film covering the surface of the object is an adhesive layer constituting a single-sided adhesive sheet with a substrate, and the adhesive layer is subjected to a water supply-freezing treatment and then peeled off from the object. The adhesive layer of a commercially available single-sided adhesive sheet with a substrate (Nitto Denko Corporation's Washi Masking Tape, product name "No. 7288"), which has an adhesive layer formed from an acrylic emulsion on one side of a Japanese paper substrate, was pressed onto the surface of a stainless steel plate (SUS430BA plate) as an adherend by rolling a 2 kg roller back and forth once. This was used as a sample for evaluating peelability. The releasability after water supply-freezing treatment and the initial releasability of the above sample were compared in the same manner as in Example 3. It was confirmed that the releasability of the above single-sided PSA sheet from the substrate was clearly improved by subjecting the above sample to water supply-freezing treatment.
[0117] Although specific examples of the present invention have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and changes of the specific examples exemplified above. [Explanation of symbols]
[0118] 100 Protective film 200 Semiconductor wafers (objects)
Claims
1. A method for peeling off a protective film covering a surface of an object from the object, the protective film being a film containing a resin material, The method includes supplying water to the protective film and then performing a freezing treatment.
2. The peeling method according to claim 1 , wherein the protective film is a film formed from a water-dispersible resin composition.
3. The peeling method according to claim 1 or 2, wherein the protective film has a water absorption rate of more than 3% based on the water absorption rate measurement described below. [Water absorption measurement] A sample having the protective film provided on the surface of a flat glass plate is immersed in ion-exchanged water at 23° C. for 30 minutes, and the water absorption rate is calculated from the weight W0 of the protective film before immersion and the weight W1 of the protective film after immersion according to the following formula. Water absorption rate [%] = (W1-W0) / W0×100
4. The peeling method according to claim 1 or 2, wherein the protective film has a tensile modulus of elasticity of 10 MPa or more at 23°C.
5. The peeling method according to claim 1 , wherein the surface of the object has a plurality of projections and recesses.
6. 3. The peeling method according to claim 1, wherein the surface of the object is a surface of a semiconductor wafer on which a circuit pattern is formed.
7. covering the surface of the semiconductor wafer on which the circuit pattern is formed with a protective film containing a resin material; grinding the surface of the semiconductor wafer not covered by the protective film; providing water to the protective film and then subjecting it to a freezing treatment; and peeling and removing the protective film that has been subjected to the freezing treatment; A method for processing a semiconductor wafer, comprising:
Citation Information
Patent Citations
Resin composition for silicon wafer protection film
JP1998120965A
Polishing method and cleaning method of wafer and protection film
JP2000315668A
Hybrid backlight
JP2011023272A
Copper alloy material having excellent strength and plating property and production method thereof
JP2014019889A
Composition for forming protection film, method of forming protection film, protection film, and method of removing protection film
JP2014212179A